Mao's steps in Monroe's backyard: towards a United States-China hegemonic struggle in Latin America? - León-Manríquez,Jose (2014)
Contrary to what could be expected given the United States' historical hegemony of Latin America, growing Chinese influence in this region has not led to a dispute between China and the US. Despite activism of hard-line groups in the United States, both parties have faced the issue with noticeable pragmatism. This attitude could be explained by three variables: the US political negligence towards Latin America in the Post-Cold War, the focus of Sino-Latin American relations on economic rather than geopolitical or ideological affairs, and the scanty relevance of the region in the top priorities of overall Washington-Beijing relations.